A starvation-induced noncoding RNA modulates expression of Dicer-regulated genes - Hellwig, Sabine (National Academy of Sciences, 2008)
Although much has been learned about short noncoding RNAs, long noncoding transcripts are largely uncharacterized. Here, we describe Caenorhabditis elegans rncs-1, a highly base-paired, 800-nucleotide noncoding RNA expressed in hypodermis and intestine. Transcription of rncs-1 is modulated in response to food supply. Although highly double-stranded, we show that rncs-1 RNA is not a substrate for Dicer because of branched structures at its termini. However, rncs-1 RNA inhibits Dicer cleavage of a second dsRNA in vitro, presumably by competition. We validate this observation in vivo by demonstrating that mRNA levels of several Dicer-regulated genes vary with changes in rncs-1 expression. Certain viruses express dsRNA to compete with cellular dsRNA-mediated pathways, and our data suggest that rncs-1 provides a cellular correlate of this phenomenon.